Review of Chinese Policy Against Cryptocurrency Growth - Yaning Cheng (GoAcademica Research & Publishing, 2019)
The development of financial technology arrived at a new form, namely cryptocurrency. The development of cryptocurrency with an increasingly widespread network and its autonomous nature cannot be controlled by the state, which makes China implement policies to block all domestic cryptocurrency activities. The policy becomes unnatural when China occupies the top position in the developing global digital currency market. This anomaly is interesting to study further to find reasons that motivate China to take firm policy when in a safe position as a center of production and global crypto currency transactions. To explain this reason, national interest theory and rational choice are used as the main tools in analyzing this problem. The national interest theory and rational choice explain that the policies taken by China are motivated by economic and security interests, as well as rational calculations of the advantages and disadvantages of those policies